Bacillus anthracis Protective Antigen Shows High Specificity for a UV Induced Mouse Model of Cutaneous Squamous Cell Carcinoma - Crawford, Theo; Fletcher, Nicholas; Veitch, Margaret; Gonzalez Cruz, Jazmina L.; Pett, Nicola; Brereton, Ian; Wells, James W.; Mobli, Mehdi; Tesiram, Yasvir (Frontiers in Medicine, 2019)
Squamous cell carcinoma (SCC) accounts for the majority of non-melanoma skin cancer related deaths, particularly in immunosuppressed persons. Identification of biomarkers that could be used to identify or treat SCC would be of significant benefit. The anthrax toxin receptors, Tumor Endothelial Marker 8 (TEM8) and Capillary Morphogenesis Gene 2 (CMG2), are endothelial receptors involved in extracellular matrix homeostasis and angiogenesis that are selectively upregulated on numerous tumors. One method of targeting these receptors is Protective Antigen (PA), a protein produced by B. anthracis that mediates binding and translocation of anthrax toxins into cells. PA targeted toxins have been demonstrated to selectively inhibit tumor growth and angiogenesis, but tumor selectivity of PA is currently unknown. In this work fluorescently labeled PA was shown to maintain receptor dependent binding and internalization in vitro. Utilizing a human papillomavirus transgenic mouse model that develops cutaneous SCC in response to ultraviolet irradiation we identified tumor uptake of PA in vivo. The intravenously administered PA resulted in tumor specific localization, with exclusive tumor detection 24 hours post injection. Ex vivo analysis identified significantly higher fluorescence in the tumor compared to adjacent healthy tissue and major clearance organs, demonstrating low non-specific uptake and rapid clearance. While both TEM8 and CMG2 were observed to be overexpressed in SCC tumor sections compared to control skin, the intravenously administered PA was primarily co-localized with TEM8. These results suggest that PA could be systemically administered for rapid identification of cutaneous SCC, with potential for further therapeutic development.